Cognitive Functioning and Pain Reactions in Hospitalized Elders - Thomas Hadjistvropoulos; Diane LaChapelle; Farley MacLeod; Carla Hale; Norm O’Rourke; Kenneth D Craig (Pain Research and Management)
BACKGROUND: Objectively coded facial activity provides a useful index of pain among elders who have difficulty in reporting pain because of cognitive impairments. However, limitations of previous research include no direct assessment of participants' level of cognitive impairment; no comparison of the reactions of elders with cognitive impairments with those of nonimpaired elders; observers' expectations about pain levels could have influenced judgements about the severity of pain experienced when global rather than objectively coded measures were used because the painful medical procedure was visible on film.